Natural history of early gastric cancer: series of 21 cases - Iwagami, Hiroyoshi (Endosc Int Open, 2019)
Background and study aims  While knowledge of the natural history of early gastric cancer (EGC) may be useful in relevant clinical situations, few relevant reports are available. Therefore, we investigated the progression of EGC. We gathered data regarding 114 cases of EGC from 2005 to 2015 from a hospital cancer registry and analyzed 21 lesions that fulfilled five inclusion criteria. Deep progression was defined as submucosal invasion by a mucosal tumor and proper muscle invasion by a submucosal tumor. Lateral progression was defined as ≥ 20 % increase in size. During median follow-up of 23 months, one of 18 mucosal tumors showed deep progression and six showed lateral progression. Of three submucosal tumors, two showed deep progression and three showed lateral progression. Our study suggests that a certain proportion of mucosal cancers can lie dormant for several years. Further large-scale studies in a multicenter setting should overcome the limitations of this study.